Winckelmann and the invention of antiquity history and aesthetics in the age of Altertumswissenschaft - Harloe, Katherine 1978- (Classical presences, 2013)
"This volume provides a new perspective on the emergence of the modern study of antiquity, Altertumswissenschaft, in eighteenth-century Germany through an exploration of debates that arose over the work of the art historian Johann Joachim Winckelmann between his death in 1768 and the end of the century. Winckelmann's eloquent articulation of the cultural and aesthetic value of studying the ancient Greeks, his adumbration of a new method for studying ancient artworks, and his provision of a model of cultural-historical development in terms of a succession of period styles, influenced both the public and intra-disciplinary self-image of classics long into the twentieth century. Yet this area of Winckelmann's Nachleben has received relatively little attention compared with the proliferation of studies concerning his importance for late eighteenth-century German art and literature, for historians of sexuality, and his traditional status as a 'founder figure' within the academic disciplines of classical archaeology and the history of art."--Provided by publisher